PENGEMBANGAN E-LKPD MATA PELAJARAN BAHASA INDONESIA PADA ELEMEN MEMBACA DALAM KURIKULUM MERDEKA DI KELAS IV SEKOLAH DASAR - Lika Apreasta; Ratnawati; Haziatun Syakira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by problems with student worksheets that still use printed worksheets that are less attractive. Efforts to overcome the problem are developing E-LKPD which is assisted by the liveworksheet application. The research aims to produce E-LKPD products. This type of research is research (R&D) using the 4D development model which consists of several stages: definition, design, development and deployment. The test subjects were grade 4 students at SDN 10 Koto Baru, Dharmasraya Regency. Assessment instruments in the form of validation, practicality, effectiveness. The assessment instrument was validated by three validators, content, language and graphics, then the practicality sheet was determined by the practitioner. And the effectiveness is determined from the learning outcomes of class IV students. The results of the validity of the E-LKPD carried out by three validators obtained an average validity value of 90% categorized as very valid, the average teacher practicality value 90% categorize as very valid. and the average student practicality value - an average of 83% is categorized as very practical and the student effectiveness value of 83.33% is categorized as very effective. It can be concluded that the E-LKPD for Indonesian subjects produced meets the valid category, meaning that it can be applied by students, the category is very practical, it means that it is easy to use by students, and the category is very effective, it means that the E-LKPD for Indonesian subjects can achieve student learning objectives.